Practical Synthesis of N-Anilinylphenothiazines Using a Cyclic Hypervalent Iodine Coupling Reagent - Yanase, Kana; Morimoto, Koji; Dohi, Toshifumi; Kita, Yasuyuki (Synthesis, 2024)
An improved protocol for the synthesis of N-anilinylphenothiazines based on the coupling reaction of anilines with phenothiazines using cyclic iodine(III) reagent is presented. In the improved method, the product can be isolated and purified without using column chromatography, and the cyclic hypervalent iodine reagent can be quantitatively recovered by aliquot manipulation. The workup procedure presented here is simpler compared to previously reported ones, facilitating large-scale synthesis. The para-selective phenothiazination of nitrogen-containing heterocycles such as hydroquinoline, which is important in pharmacology, was also successfully performed.
Keywords: hypervalent iodine(III) reagent; aryl C–H amination; solid–liquid separation; coupling reaction; N-anilinylphenothiazines